2005
DOI: 10.1007/s00380-005-0841-9
|View full text |Cite
|
Sign up to set email alerts
|

Taurine prevents myocardial ischemia/reperfusion-induced oxidative stress and apoptosis in prolonged hypothermic rat heart preservation

Abstract: Taurine (2-aminoethanesulfonic acid) is a potent antioxidant and inhibits cell apoptosis in ischemic reperfusion injury. In this study we evaluated whether addition of taurine to St. Thomas' cardioplegic solution enhances its myocardial protective effects in prolonged hypothermic heart preservation in rats. Hearts isolated from male Sprague-Dawley rats were mounted on a Langendorff apparatus to estimate baseline cardiac function, then arrested and stored in St. Thomas' cardioplegic solution, with taurine (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 47 publications
5
34
0
1
Order By: Relevance
“…Consistent with other findings, 13,14,16) our data reveals that Tau protects cardiomyocytes against H2O2-induced apoptosis. The production of LDH is an important parameter that indicates cell membrane injury.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with other findings, 13,14,16) our data reveals that Tau protects cardiomyocytes against H2O2-induced apoptosis. The production of LDH is an important parameter that indicates cell membrane injury.…”
Section: Discussionsupporting
confidence: 93%
“…12) Tau attenuates myocardial apoptosis induced by Ca 2+ overload or ischemia-reperfusion injury. 13) The mechanism underlying the anti-apoptotic action of Tau is related to the regulation of L-type Ca 2+ channels and Ca 2+ -ATPase-mediated Ca 2+ uptake, 14,15) which is associated with the apoptotic pathway. 16) However, the mechanisms underlying cardiac protection by Tau are not understood completely.…”
mentioning
confidence: 99%
“…Explanted hearts from rats fed on a diet with high taurine content showed increased resistance to ischemic damage (58). Furthermore, storage of fresh rat hearts in a solution with taurine significantly improved preservation of the rat hearts by lowering DNA oxidative stress and apoptosis (48). These results indicate that taurine might have protective effects against hypoxic/ischemic damage.…”
mentioning
confidence: 90%
“…Milei et al (1992) found that rapid infusion of 5 g of taurine before bypass surgery provided protection against reperfusion injury. Moreover, taurine treatment was found to diminish damage to arrested hearts during cold isotonic storage prior to transplant (Sahin et al 2011;Oriyanhan et al 2005). The field awaits further evaluation of taurine's effect.…”
Section: Introductionmentioning
confidence: 99%